(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Polozenko O. Criteria and indicators of psychological readiness of future specialists of agrarian industry for professional activity. The article illustrates the problem of the basic concepts of forming students’ reflexive abilities in Pedagogical University in the process of self-directed (independent) educational activity